2018
DOI: 10.1116/1.5026405
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition of CeO2 using a heteroleptic cyclopentadienyl-amidinate precursor

Abstract: Cerium oxide thin films were deposited on fused silica using atomic layer deposition (ALD). The novel Ce precursor, Ce(iPrCp)2(N-iPr-amd) [bis-isopropylcyclopentadienyl-di-isopropylacetamidinate-cerium] is a room-temperature liquid with good thermal stability and evaporates cleanly. Water vapor was used as the oxygen source. The growth characteristics and film properties of ALD CeO2 were investigated. A relatively broad ALD window of 165–285 °C resulted in a constant growth rate of 1.9 Å/cycle and good thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Addressing this crucial shortcoming, heteroleptic Ce complexes with Cp and amidinate ligands [30] were introduced as ALD precursors. They possess higher thermals tabilitya nd volatility than the homoleptic RE-Cp 3 complexes and are reactive towards water.F urthermore, the precursors are liquid at room temperature and can be evaporated at 145 8Ci nc ase of the [CeCp 2 (iPr-AMD)] [bisisopropylcyclopentadienyl-N,N'-diisopropylacetamidinate-cerium(III)] [31] However,t he preparationo ft hese precursors is an intricateprocess and generally delivers low yields.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing this crucial shortcoming, heteroleptic Ce complexes with Cp and amidinate ligands [30] were introduced as ALD precursors. They possess higher thermals tabilitya nd volatility than the homoleptic RE-Cp 3 complexes and are reactive towards water.F urthermore, the precursors are liquid at room temperature and can be evaporated at 145 8Ci nc ase of the [CeCp 2 (iPr-AMD)] [bisisopropylcyclopentadienyl-N,N'-diisopropylacetamidinate-cerium(III)] [31] However,t he preparationo ft hese precursors is an intricateprocess and generally delivers low yields.…”
Section: Introductionmentioning
confidence: 99%
“…/cycle using a novel heteroleptic cyclopentadienyl-amidinate precursor Ce(iPeCp)2(N-iPramd). 30 However, the synthesis of heteroleptic cerium complex is rather difficult.…”
Section: Discussionmentioning
confidence: 99%
“…24 A growth rate of 1.9 /cycle is found at growth temperatures of 165 -285 °C using a heteroleptic cyclopentadienyl-amidinate precursor Ce(iPeCp)2(N-iPr-amd). 30 However, the synthesis of heteroleptic cerium complex is rather difficult. The development of efficient and convenient CeOx precursors is still required.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has been focusing on metal acetamidinates as prototypical systems to extract general information on chemical systems relevant to CVD and ALD. ,,,,,, Acetamidinate ligands have proven to be quite ubiquitous, given that they can be used to make complexes with a large number of metals , and are promising as film deposition precursors because their physical properties (stability, vapor pressure, etc.) can be tuned by tinkering with the substitution groups added. Our experimental work has shown that copper acetamidinates, stable under most conditions in solid, liquid, or gas phases, are nevertheless fairly reactive on solid surfaces, especially on those of late transition metals. Specifically, we have identified the beta-hydrogen position on the side moieties of most acetamidinates as a particular labile and reactive site leading to undesired decomposition. ,, We have also addressed the additional complication that arises from the fact that many metal acetamidinates form dimers or other oligomers when in solid or gas phases. ,,,,,, Dissociation of those into monomers upon adsorption onto solid surfaces compete with molecular desorption and/or unique decomposition routes stabilized by the dimeric structures.…”
Section: Introductionmentioning
confidence: 99%